Successful Eltrombopag Therapy in a Child with MYH9-Related Inherited Thrombocytopenia - Giuseppe Lassandro; Francesco Carriero; Domenico Noviello; Valentina Palladino; Giovanni Carlo Del Vecchio; Maria Felicia Faienza; Paola Giordano (MDPI AG, 2022)
Inherited thrombocytopenias represents a heterogenous group of diseases characterized by a congenital reduction in the platelet count that could lead to a bleeding tendency. MYH9-related disorders are characterized by large platelets and congenital thrombocytopenia. Thrombopoietin-receptor agonists: eltrombopag and romiplostim are currently approved in many countries for the treatment of different forms of acquired thrombocytopenia, such as immune thrombocytopenia. We report, instead, the successful use of eltrombopag to treat inherited thrombocytopenia in a patient with an MHY9-related disease. This is the first report of a chronic use of eltrombopag to elevate platelets in MYH9-related disorders without side effects.